Learning Literacy And Numeracy Through Fun Learning Approach - Agustin, Zulva Awalia; Assidiq, Syahrul; Ripaldi, Ripaldi; Nurulaeni, Fitria; Hopeman, Teofilus Ardian (Universitas Mercu Buana, 2024)
The challenge of improving literacy and numeracy is still a major focus in many countries, including Indonesia. Based on the Program for International Student Assessment (PISA) in 2022, the results of the evaluation of the literacy and numeracy skills of students in Indonesia again showed a disappointing ranking. This is in line with the problems found at the community service location, namely low student interest in reading. So this research has a goal as a community service effort to improve and optimize students' literacy and numeracy skills through a fun learning approach. This community service activity was carried out at SDN Gunung Sunda which is located in Cikakak District, Sukabumi Regency, West Java. The community service methods used are observation, lecture, and training methods. The results obtained in this study are students are more fond of reading and motivated in terms of literacy and numeracy by using a fun learning approach.